Opportunities and Challenges for Promoting Sustainable Water Services to the Urban Poor in Dhaka City - Roy, S; Dutta, S (Journal of Environmental Science and Natural Resources, 2018)
Dhaka is one of the densely populated megacities in developing countries with rapidly growing urban population. A significant portion of Dhaka’s population lives in informal settlements and is truly deprived of adequate water services. The study was intended to explore obstacles behind promoting sustainable water services to urban poor in Dhaka city as well as to find out opportunities in this regard. A questionnaire survey was conducted amongthe officials of 3 government organizations and 3 non-governmental organizations. In Dhaka city, water services provided by the Dhaka Water Supply and Sewerage Authority is largely groundwater dependent, and a small amount of supplied water comes from surface water sources. The study revealed that compare to rising water demands, supply is absolutely unsatisfactory to city dwellers mainly due to poor infrastructures, lack of sustainable planning and management practices, population pressure and financial constraints. The study showed that conjunctive use of surface water and rainwater, with limited extraction of ground water could be better way for providing sustainable water services to urban poor in Dhaka city. Moreover, effective coordination between government organizations & NGOs and incorporation of private sectors and local community in the service sectors can help to provide sustainable water services. J. Environ. Sci. & Natural Resources, 10(2): 1-10 2017